Les Rois mages. Iconographie et art monumental dans l’espace féodal (xe-xiie siècle) - Mathieu Beaud (Bulletin du Centre d’Études Médiévales d’Auxerre)
This dissertation deals with the iconography of the Three Kings from the 10th to the 12th century, by means of a study of its adaptation on monumental decoration in Latin Europe, so as to unravel how it was adapted by feudal society. The aim is to define where the newly defined Three Kings stand in the intricate network of “ties between man and man” theorized by Marc Bloch. A phenomenological analysis reveals the features of the characters in the “feudal imaginary”, fully invested with their royal function and its aura, and finding their place in a mental system whose mode of functioning can be unveiled thanks to the study of great iconographic sets. Being abstract universal figures, the Three Kings constitute a clear picture of the notion of social group, modulated according to various unifying consciences, from the most basic unit to Christian Holism.